Philippine Cultural Studies in Focus Localizing the Global, Globalizing the Local - Fernandez, Steven Patrick C. (Langkit : the Official journal of the College of Arts & Social Sciences Mindanao State University-Iligan Institute of Technology, 2013)
Culture can only be understood through overarching disciplines. One discipline cannot be fragmented from the other. Like the nation, culture is composed of various parts, each will own its synthetized relationship with the other parts producing causal relationships acting on all the others.